2019
DOI: 10.33233/fb.v20i4.2299
|View full text |Cite
|
Sign up to set email alerts
|

Insuflador-exsuflador mecânico versus manobra PEEP-ZEEP em pacientes em ventilação mecânica prolongada

Abstract: Introdução: A presença da via aérea artificial, associada com a imobilidade no leito, resulta em um déficit na desobstrução das vias aéreas em pacientes sob ventilação mecânica (VM). Tal condição contribui para o desenvolvimento de quadros de hipoxemia e/ou infecções respiratórias, aumentando o trabalho respiratório e também as falhas de extubação. Objetivo: Comparar os efeitos da utilização do insuflador-exsuflador mecânico e da manobra PEEP-ZEEP em relação à mecânica respiratória em pacientes ventilados meca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Most studies (no. ¼ 9) were randomized controlled trials (5 full-text publications, [20][21][22][23][24] 3 trial registrations, [25][26][27] and one abstract 28 ) or descriptive studies (no. ¼ 19) including observational cohort studies (no.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most studies (no. ¼ 9) were randomized controlled trials (5 full-text publications, [20][21][22][23][24] 3 trial registrations, [25][26][27] and one abstract 28 ) or descriptive studies (no. ¼ 19) including observational cohort studies (no.…”
Section: Resultsmentioning
confidence: 99%
“…A pause duration was reported in 8/20 (40%) studies. [20][21][22][23][24]30,34,44 Five studies (25%) reported use of one insufflation prior to an exsufflation breath (not reported in the remaining studies). Flow profile was specified in only 3 (15%) studies and was set at medium (no.…”
Section: Clinical Studiesmentioning
confidence: 99%
See 3 more Smart Citations